Conclusions of a meeting of the Cabinet held at 10 Downing Street, S.W.1, on Thursday, 4th June, 1959, at 11 a.m - Great Britain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1959)
Cabinet papers dealing with various issues including the death of 11 Mau Mau prisoners at Hola Detention Camp, Kenya, March 1959